(untitled) (Research, Society and Development, 2020)
Medicines are chemicals that are manipulated to bring therapeutic effects to people. Every day it is possible to observe its importance in society, either helping in the treatment of some pathology or favoring a better quality of life. The present study aimed to evaluate the effects caused by the disposal of medicines in the environment. In order to carry out the present study, a bibliographic survey was carried out in the Medline, VHL and Pubmed databases, from 2014 to 2020, in the English and Portuguese languages that fit the inclusion and exclusion criteria, 10 articles were selected. In all the studies evaluated, the authors unanimously concluded that the majority of the population is unaware of the means of correctly disposing of medicines and the harmful impacts they cause on the environment. Therefore, this review demonstrated that despite having several studies on this issue, there is still a great lack of information regarding the population.